PENGGUNAAN PROBIOTIK DALAM BUDIDAYA TERNAK - Permadi, Angga; Izza, Mubalikhoh Aqidatul; Cahyo, Kukuh; Kholif, Muhammad Al (Jurnal Abadimas Adi Buana, 2018)
Probiotics are certain microorganisms that exist in the animal's body and will guarantee the effective formation of beneficial organisms in the host's body (animals) especially the digestive system because it can improve the balance of the intestinal microflora. Probiotics contain beneficial bacteria that are inserted into the digestion to dominate bacteria that cause decreased (pathogenic) disease. Probiotics can contain one or several strains of similar microorganisms. Shaped powder, tablets, solid round shape (granules), and like a mixture of some soft ingredients (pasta). Biotics work by suppressing microbial populations through competition by producing antimicrobial compounds or through nutritional competition, changing microbial metabolism by increasing or decreasing enzyme activity and stimulates immunity through increased levels of antibodies or large cell activity that is capable of digesting bacteria and large amounts of cells (macrophages). Probiotics aim to improve the condition of the digestive tract by suppressing the reaction of the formation of toxins and metabolites that are ingredients that can encourage or cause cancer (carcinogenic), stimulate enzyme reactions that can neutralize toxic compounds that are ingested or produced by the digestive tract, stimulate the production of enzymes needed to digest food and produce vitamins and substances that are not fulfilled in feed. The results obtained begin to be used after a fragrant smell like tape comes out of the liquid and there is a gas bubble. Probiotics that are diluted or reproduced here are of the type of probiotics mixed into the feed. Before use, this new probiotic also needs to be diluted first with water. The volume used is more than the volume when the original probiotic is used. In addition to increasing the volume of probiotic liquid until it can be used longer, the addition of drops to the probiotic is also intended to increase the activity of bacteria in it.